SASTRA LISAN SEBAGAI KEKUATAN KULTURAL DALAM PENGEMBANGAN STRATEGI PERTAHANAN NASIONAL DI PELABUHAN RATU JAWA BARAT - Dana Waskita; Tri Sulistianingtyas; jejen Jaelani (Fakultas Seni Rupa dan Desain ITB, 2011)
Oral literature has an important role in the formation of values in society. Oral literature in Pelabuhan Ratu has an important role in community life. Oral literature in this study was examined using a qualitative approach. Oral literature in Pelabuhan Ratu not only serves as entertainment or education, but it has also broader function in life. One of the functions of oral literature is to establish the identity and integrity of a society. Oral literature in Pelabuhan Ratu has become such a public binder that the community has the resilience of the various threats that come both from outside and from inside. Oral literature has become a stronghold guarding the public from the threat of swift and eroding cultural values in society. If it is maintained and enhanced, this will contribute in the development of a national defense strategy in general. Key words: oral literarure, Pelabuhan Ratu, identity